Library service quality and users’ satisfaction: a correlational study among UiTM Puncak Perdana students / Muniratul Husna Mohamad Zaki ... [et al.] - Mohamad Zaki, Muniratul Husna; Hasan, Hazlin; Syed Wahid, Sharifah Norhuda; Mohamad, Mastura (Universiti Teknologi MARA, Perlis, 2023)
A library is an organization that provides its services and facilities to the community to gain knowledge and eases the users to get the information needed according to their needs. UiTM libraries, belonging to the largest public university in Malaysia, have a tremendous challenge in ensuring that they serve the right resources to their users at the right time and fulfil their users’ satisfaction that relies upon the quality of services provided by them. Hence, the objective of this study is to assess the perceived service quality of PTAR UiTM Puncak Perdana services and facilities on users’ satisfaction. A total of 397 students of UiTM Puncak Perdana Campus, who use the library services, were randomly selected to participate in a survey using the SERVQUAL questionnaire which was distributed and collected personally by the researchers. A correlational analysis between SERVQUAL dimensions and users’ satisfaction was conducted using the IBM-SPSS AMOS version 24.0. This study revealed that there is a moderate positive relationship between all service quality dimensions and user satisfaction. It was concluded that service quality had a significant and positive impact on students’ satisfaction. Research has proven that student satisfaction is a good indicator of a university’s strengths and weaknesses, and higher learning institutions place a high priority on students’ satisfaction. Therefore, it is pertinent for the university to keep track of its library’s service quality from the users’ perspective regularly and ensure a high-quality service and facilities are available to fulfil its users’ satisfaction. More elaborated research on other related perspectives of users’ satisfaction with the library’s services and facilities may be conducted in the future to ensure that the libraries stay in demand and relevant despite the fastrevolving information technology.